Spectrum of breast diseases in a rural himalayan region of Western Nepal: a hospital based study - Devkota, Harihar; Menyangbo, Suryaman; Amgain, Kapil (Journal of Chitwan Medical College, 2020)
Background: Breast diseases, among the most common diseases in females occur in various patterns from benign to malignant. Their identification is crucial as some of the benign disorders pose threat to turn into malignancy. This study was aimed to determine the spectrum of breast diseases. Methods: This was a hospital based retrospective study among all the patients in General Surgery OPD of Karnali Academy of Health Sciences, Teaching Hospital, diagnosed with breast diseases during one year period from August 2019 to July 2020 AD. Data were extracted and entered in SPSS version 16 for further analysis. Results: Out of 110 cases, only 4 (3.96%) were male. Almost half 54 (49.09%) of the cases were in the age group of 21-30 years. Fibrocystic disease, Breast Abscess and fibroadenoma, and cracked nipple were 39 (35.45%), 38 (34.54%, 15 (13.63%) and 8 (7.28%) respectively. The benign diseases were seen mostly in the younger population while malignant breast diseases were seen in the older population. Mastalgia was mostly seen in the twenties (17.3%) and the thirties (10%) while Breast abscess was commonly encountered in the twenties (16.4%) and the teens (11.8%). The gynaecomastia were seen only in four males. Conclusions: Fibrocystic breast diseases, Mastitis with or without abscess, fibroadenoma and cracked nipples were the first four most common breast diseases in females. The younger population had predilection towards the benign diseases which occurred most frequently in the third decade while the malignant occurred in sixth and seventh decade.